Neuropeptide w alleviates hepatorenal oxidative damage in sepsis-induced rats - ATICI, ALİ EMRE; PEKER EYÜBOĞLU, İREM; ERCAN, FERİHA; AKKİPRİK, MUSTAFA; YEGEN, BERRAK (My University, 2020)
Background: Despite modern surgical, medical and intensive care treatments, sepsis is still one of the most frequent causes of morbidity and mortality due to multiple life-threatening organ dysfunctions. We aimed to investigate the possible protective effect of neuropeptide W (NPW), a novel peptide effective in regulating neuroendocrine functions, against sepsisinduced hepatorenal damage. Methods: In male Sprague-Dawley rats (200–250 g), sepsis was induced by cecal ligation and puncture under ketamine anesthesia (n=48). Immediately after surgery, saline or TNF-alpha inhibitor (etanercept; 1 mg/kg) plus antibiotic (ceftriaxon; 100 mg/kg) (ET+C) or NPW (0.1, 0.3, 1 or 3 mg/kg) was given subcutaneously, and repeated at 12th and 24th hours, while sham-operated control group (n=8) received three saline injections within twenty-four hours. Rats were decapitated at the 25th hour of surgery and C-reactive protein (CRP), corticosterone and IL-6 levels were measured in serum samples. Kidney and liver samples were obtained for the measurement of myeloperoxidase activity (MPO), malondialdehyde and glutathione levels and nuclear factor kappa-B (NF-kB) mRNA expression levels. Histopathological evaluations were performed in hematoxylin-eosin-stained samples. ANOVA and Student's t-tests were used for data analysis. Results: Elevated serum levels of IL-6, corticosterone and CRP (p<0.05-0.01) in saline-treated sepsis group, as compared to controls, were depressed in the ET+C- (p<0.05) or NPW- (p<0.05-0.001) treated groups. Hepatic malondialdehyde and MPO levels, which were increased in salinetreated sepsis group (p<0.05 and p<0.001), were decreased by ET+C- (p<0.01) or NPW (p<0.05-0.001) treatments. Similarly, increased renal malondialdehyde level was depressed by NPW (p<0.05), but not by ET+C; while none of the treatments had an inhibitory effect on renal MPO. In contrast to replenished renal glutathione levels by all treatments, hepatic glutathione content was not changed by any of the treatments. Hepatic and renal NF-kB mRNA expressions were similar in all groups. Severe hepatocyte degeneration, sinusoidal congestion and inflammatory cell infiltration were observed in saline-treated sepsis group, while parenchymal degeneration, congestion and Kupffer cell activation were mild in ET+Cand NPW-treated sepsis groups. Similarly, severe degeneration of renal corpuscles and tubules with glomerular and interstitial congestion in the saline-treated sepsis group was replaced by moderate glomerular and interstitial vascular congestion and mild tubular congestion in both NPW- and ET+C-treated groups. Conclusion: NPW, applied during the first 24 hours of sepsis, exerted a dose-dependent protective effect against hepatorenal damage, which appears to involve an inhibitor